Cost-Effectiveness of Peer-Delivered HIV Self-Tests for MSM in Uganda - Okoboi, Stephen; Castelnuovo, Barbara; Van Geertruyden, Jean-Pierre; Lazarus, Oucul; Vu, Lung; Kalibala, Sam; Kamara, Yvonne; Ochanda, Perez N.; King, Rachel; Mujugira, Andrew (Frontiers in Public Health, 2021)
Introduction Distribution of HIV self-testing (HIVST) kits through MSM peer networks is a novel and effective strategy to increase HIV testing coverage in this high-risk population. No study has evaluated the cost or cost effectiveness of peer distribution of HIVST strategies among MSM in sub-Saharan Africa. Methods From June to August 2018, we conducted a pilot study of secondary MSM peer HIVST kit distribution at The AIDS Support Organization (TASO) Entebbe and Masaka. We used an ingredients approach to estimate the cost of MSM peer HIVST kit distribution relative to standard-of-care (SOC) hotspot testing using programme expenditure data. The provider perspective was used to estimate incremental cost-effective ratios (ICER) per HIV infection averted using the difference in HIV annual transmission rates between MSM with HIV who knew their status and were not virologically suppressed and MSM with HIV who did not know their status. Results We enrolled 297 participants of whom 150 received MSM peer HIVST kit distribution (intervention group) and 147 received TASO standard of care (SOC) HIV testing (control group). Provider cost for MSM peer HIVST kits distribution was 2,276 compared with 1,827 for SOC during the 3-month study period. Overall, the intervention resulted in higher HIV positivity yield (4.9% vs. 1.4%) and averted more HIV infections per year (0.364 vs. 0.104) compared with SOC. The cost per person tested was higher for the intervention compared to SOC (15.90 vs 12.40). Importantly, the cost per new HIV diagnosis (324 vs. 914) and cost per transmission averted (62.50 vs. 176) were lower for the intervention approach relative to SOC. The incremental cost per HIV transmission averted by the self-testing program was 1727. The incremental cost to providers per additional HIV-positive person identified by the intervention was 147.50. Conclusion The intervention strategy was cost-effective, and identified more undiagnosed HIV infections than SOC hotspot testing at a cost‐effectiveness threshold of US 2,129. Secondary distribution of HIVST kits through peers should be scaled up for MSM with the aim of diagnosing 95% of all persons with HIV by 2030; the first UNAIDS 95-95-95 target.